Effect of Fertilizers on The Productivity of Plants Under Different Ecological Conditions - Bagirova Bahruyya; Eyubova Svetlana; Bagirov Hasil; Hashimova Arzu (BIO Web of Conferences)
In order to obtain a high and stable yield of wheat, corn, potato and sugar beet plants in different regions of Azerbaijan, it is necessary to select high-quality seed material, study the biological characteristics of these plants, soil and climatic conditions, and carry out timely and high-quality agrotechnical measures. The application of the results and recommendations from experiments conducted in our republic on farms demonstrates that it is possible to grow high-quality wheat, corn, potatoes, and sugar beets in various regions of Azerbaijan, thereby meeting the population's year-round demand for these crops. The purpose of the research is to improve the fertilization system based on calculations of soil fertility and the balance of nutrients of various agricultural plants in various zones of the country, taking into account the ecological balance. The methodology of the work consisted of field, laboratory experiments and analytical work. In field experiments, plant care and agrotechnical measures (except for seeding) were carried out in accordance with the adopted agrotechnical rules for experimental plants. Organic, mineral and micro fertilizers were used in the research. In order to eliminate the lack of nutrients in the soil, the effect of various rates and ratios of mineral, organic and micro fertilizers on plant productivity was studied. As a result, the preservation of environmental conditions, soil fertility, increased crop yields and improved quality indicators were achieved.